Mechanochromic composite elastomers for additive manufacturing and low strain mechanophore activation. Issue 44 (18th September 2019) - Rohde, Rachel C.; Basu, Amrita; Okello, Lilian B.; Barbee, Meredith H.; Zhang, Yudi; Velev, Orlin D.; Nelson, Alshakim; Craig, Stephen L.
Abstract : Composite silicone inks provide access to 3D-printable elastomers that are mechanochemically active at lower strains that single component analogs. Abstract : Herein, we report a strategy for additive manufacturing of a mechanochemically active silicone ink primarily composed of PDMS microbeads. Extruded, stable structures of cured microbeads were held together with a "bridging material" comprising uncured PDMS and spiropyran in a water medium. The mechanochromic silicone ink was a shear-thinning gel that exhibited a yield stress, and thus, was suitable for direct-write 3D printing. The spiropyran was stable to mild conditions of the printing process, and after a thermal curing step, the printed silicone displayed reversible mechanochromic activity. The extruded composite displays chromophore activation at lower mechanical strains under uniaxial tension (60–70%) than in a film without the microbeads (130–140%). Multi-layered 3D printed constructs were fabricated and displayed mechanochromic activity in tension and compression. These experiments demonstrate the versatility of these silicone inks to produce 3D printed functional elastomers with mechanochemical activity.